2020
DOI: 10.1111/and.13903
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous leaf extract ofMoringa oleiferareduced intracellular ROS production, DNA fragmentation and acrosome reaction in Human spermatozoa in vitro

Abstract: The effects of aqueous leaf extract of Moringa oleifera (MO) on human sperm functions and integrity was studied in vitro. Semen was obtained by masturbation after 3-5 days' abstinence from 34 healthy donors in Western Cape, South Africa. Liquefied semen was washed in human tubular fluid supplemented with 1% bovine serum albumin (HTF-BSA;1:5) with 10 min centrifugation at 300 g. Sperm suspensions were subsequently incubated with MO extract (0.625, 6.25, 62.5 and 625 µg/ ml) for 1 hr, where HTF-BSA served as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 75 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Meanwhile, the reproductive efficiency of the HFD group (G3) was generally compromised, as evidenced by the significant reduction in serum testosterone, and quantitative sperm disorders (reduced sperm cell concentration) and qualitative sperm disorders (reduced sperm viability and motility, and an increased proportion of morphological abnormalities) in rats fed a HFD (Abdulwahab et al, 2020). In a previous study, the aqueous leaf extract of Moringa oleifera enhanced the percentage of non-capacitated spermatozoa, basic sperm functions, decreased the excess sperm free superoxide production, and maintained the acrosome reaction as well as the integrity of DNA in human (Moichela et al, 2021).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Meanwhile, the reproductive efficiency of the HFD group (G3) was generally compromised, as evidenced by the significant reduction in serum testosterone, and quantitative sperm disorders (reduced sperm cell concentration) and qualitative sperm disorders (reduced sperm viability and motility, and an increased proportion of morphological abnormalities) in rats fed a HFD (Abdulwahab et al, 2020). In a previous study, the aqueous leaf extract of Moringa oleifera enhanced the percentage of non-capacitated spermatozoa, basic sperm functions, decreased the excess sperm free superoxide production, and maintained the acrosome reaction as well as the integrity of DNA in human (Moichela et al, 2021).…”
Section: Discussionmentioning
confidence: 79%
“…A testicular tissue sample weighing 0.5 g was homogenised with 5 ml of refrigerated 0.1 M phosphate buffer saline (pH 7.4) using Universal Laboratory Aid homogenizer (MPW‐309, Mechanika Precyzyjna, Warsaw, Poland), filtered and centrifuged (BOECO centrifuge C‐ 28A, Hamburg, Germany) at 2,182 RCF for 15 min at 4°C. The supernatant was transferred to new tubes and kept at –20°C for bioassays (Mohamed et al., 2016). The antioxidant/oxidant levels of SOD, reduced glutathione, catalase and MDA in testicular tissue were estimated spectrophotometrically by employing specific universal kits (Bio‐diagnostic Company, Cairo, Egypt) following manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the presence of alkaloids, terpenes, and xanthones in the plant extract could enhance the aphrodisiac activity in male rats (Paz et al, 1979;Taha et al, 1995;Drewes et al, 2002;Estrada-Reyes et al, 2013). The study conducted by Moichela et al (2020) showed the antioxidant compound in aqueous extract of Moringa oleifera leaves could maintain human sperm function. Therefore, the increase of plasma testosterone level in this study might be due to the presence of these bioactive compounds in Moringa oleifera leaves aqueous extract.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects on sperm vitality, motility, acrosome reaction, and morphological parameters in the seminiferous tubules and epididymis were observed following black tea administration [137]. Both green tea and black tea decreased serum levels of alanine transaminase and aspartate transaminase but black tea only increased creatinine levels [137] Aqueous leaf extract of Moringa oleifera, the "miracle tree" containing a great number of bioactive compounds including polyphenols [138], reduced intracellular ROS production, DNA fragmentation and acrosome reaction without any effect on sperm motility, vitality, mitochondrial membrane potential and capacitation in human spermatozoa in vitro [139].…”
Section: Polyphenols and Male Fertilitymentioning
confidence: 99%